Performance of solar water heater system - 381711 Ganesan Narayanasamy (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Engineering (Mechanical-Materials)) - Universiti Teknologi Malaysia, 2004